Staphylococcus spp. Isolated from Bovine Subclinical Mastitis in Different Regions of Brazil: Molecular Typing and Biofilm Gene Expression Analysis by RT-qPCR - Priscila Luiza Mello; Danilo Flávio Moraes Riboli; Lisiane de Almeida Martins; Maria Aparecida Vasconcelos Paiva Brito; Cassiano Victória; Letícia Calixto Romero; Maria de Lourdes Ribeiro de Souza da Cunha (MDPI AG, 2020)
Bovine mastitis is mainly caused by bacteria of the genus Staphylococcus spp., which possess different virulence factors, including the capacity for biofilm formation that provides enhanced protection against the action of immune system components and serves as a barrier against the penetration of antimicrobial agents. This study aimed to characterize 181 Staphylococcus spp. Strains-including Staphylococcusaureus and coagulase-negative staphylococci (CoNS) isolated from bovine subclinical mastitis in six Brazilian states-by molecular methods. RT-qPCR was used to verify the expression of genes of the ica operon-mainly responsible for biofilm formation-as well as bap and bhp. Chromosome similarity among the isolates was investigated by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). The icaA gene was detected in 79 (43.6%) isolates, icaB in 24 (13.2%), icaC in 57 (31.4%), and icaD in 127 (70.1%). The bap gene was identified in 66 (36.4%) isolates, while the bhp gene was found in nine (4.9%). RT-qPCR confirmed the expression of the icaA gene in 60 (75.9%) isolates, of icaB in six (25%), of icaC in 26 (45.6%), and of icaD in 80 (63%). Clonal typing of the isolates by PFGE permitted the identification of eight Staphylococcusaureus clusters that simultaneously included ≥3 strains, with a similarity of ≥80%. Regarding the other species studied, three clusters were observed for Staphylococcuschromogenes and four clusters for Staphylococcusepidermidis. Only one cluster each was identified for Staphylococcussaprophyticus and Staphylococcussimulans, while the other species did not form any cluster. With respect to MLST, ST126 and ST1 were the prevalent sequence types in S. aureus, while in S.epidermidis all sequence types were different. These results reveal strains with the same evolutionary origin as other isolates, which might cause infections in humans and animals, suggesting their ability to spread between these species.